Photographic and descriptive musculoskeletal atlas of bonobos : with notes on the weight, attachments, variations, and innervation of the muscles and comparisons with common chimpanzees and humans /: with notes on the weight, attachments, variations, and innervation of the muscles and comparisons with common chimpanzees and humans. (2017) - Diogo, Rui; Shearer, Brian; Potau, Josep M; Pastor, Juan F; De Paz, Felix J; Arias-Martorell, Julia; Turcotte, Cassandra; Hammond, Ashley; Vereecke, Evie E; Vanhoof, Marie; Nauwelaerts, Sandra; Wood, Bernard
No abstract available